PEMANFAATAN LIMBAH KOTORAN SAPI SEBAGAI SOLUSI SOSIAL DAN LINGKUNGAN DALAM PEMBUATAN PUPUK ORGANIK PADAT - Nabil Tanango; Nopiana Mozin; Lucyane Djaafar (Universitas Negeri Gorontalo, 2025)
This community service activity aims to educate Kabila villagers about the use of household organic waste through the cultivation of magot (Black Soldier Fly) as an environmentally friendly and economically valuable animal feed. This Program was held on October 26, 2025 by students of the Animal Husbandry Department of Gorontalo State University with lecturers in citizenship courses and involved 45 participants from the local community. The methods used include counseling, demonstration of how to make magot media using natural ingredients (such as papaya leaves, moringa leaves, Bran, and rice washing water), and participatory practices. The results of the activity showed a successful production of 3.5 kilograms of quality magot with a cultivation success rate of 85%. The Magot was then distributed to 30 heads of farmer families as an alternative high-protein feed. The conclusion of this activity is that magot cultivation is a practical and economical solution for organic waste management while improving community skills in providing independent animal feed in line with civic values.